Mast cell concentration and skin wound contraction in rats treated with Ximenia americana L - Castro Souza Junior Neto,José de (2017)
Abstract Purpose: To evaluate wound contraction and the concentration of mast cells in skin wounds treated with wild plum (Ximenia americana) essential oil-based ointment in rats. Methods: Sixty rats were submitted to two cutaneous wounds in the thoracic region, on the right and left antimeres. Thereon, they were divided into three groups: GX (wounds treated once a day with hydro alcoholic branch extract of Ximenia americana), GP (wounds that received vehicle), and GC (wounds without product application). Wounds were measured immediately after the injury as well as 4, 7, 14 and 21 days post-topical application of the extract. At these days, five rats from each group were euthanatized. Thereafter, samples were fixed in 10% formaldehyde and processed for paraffin embedding. Sections were stained with H.E, Masson's Trichrome and toluidine blue for morphological, morphometrical and histopathological analysis, under light microscopy. The degree of epithelial contraction was measured and mast cell concentrations were also evaluated with an image analyzer (Image Pro-plus®software) . Results: The extract treated group showed lower mast cell concentrations in the 4th day of lesion, as compared to GP (GX<GP=GC, p=0.029), as well as with increased contraction at 7th and 14th days, respectively (7th and 14th days, GX > GP = GC; p<0.05) . Conclusion: Ointment containing 10% X. americana induces a decrease in mast cell concentration, at the beginning of the healing process, and promotes early skin wound contraction in rats.